ANALISIS PENGARUH EXPENSE RATIO DAN TURNOVER RATIO TERHADAP KINERJA REKSADANA SAHAM (STUDI KASUS PADA REKSADANA SAHAM SYARIAH DI OTORITAS JASA KEUANGAN (OJK) PERIODE 2018 – 2023) - Raisa Nurazizah; Tartila Devy (CV. Adiba Aisha Amira, 2025)
The purpose of this research is to find out and analyze how much influence the Expense Ratio and Turnover Ratio have on the Performance of Stock Mutual Funds. This research uses a quantitative type of research using observation and documentation data collection techniques. The pre-research test used descriptive statistics, the Classical Assumption Test used the normality test, heteroscedasticity test, multicollinearity test and autocorrelation test. Next, use the Multiple Linear Regression Test, Hypothesis Test using the T Test (Partial) and F Test (Simultaneous), and finally use the determinant coefficient test (R2). The results of data analysis carried out using SPSS Version 25, the results of data analysis obtained from the t test show tcount 0.541 ≤ ttable 2.014 with a significant value of 0.591 ≥ 0.05, so H0 is accepted and H1 is rejected, which means the variable partially does not have a significant influence on the performance of stock mutual funds. For the variable value tcount 5.201 ≥ ttable 2.014 with a significant value of 0.000 ≤ 0.05, H0 is rejected and H2 is accepted, which means the variable partially has a positive and significant influence on the performance of stock mutual funds. Judging from the f test, the calculated f value is 16.097 ≥ f table 4.05 with a significant value of 0.000 ≤ 0.05. This means that the variables together have a significant eflect on the performance of stock mutual funds. From the results, the determinant coefficient (R2) is 0.417 or 41.7%. This shows that 41.7% of mutual fund performance variables can be explained by variables and and 58.3% are influenced by other factors not discussed in this research.